Effects of deformation dynamics in problems of heavy transport - Nosachev Sergei V.; Chuveiko Mikhail V.; Zhukova Maria Yu.; Kuzin Gennadiy A.; Khozyaev Igor A. (MATEC Web of Conferences, 2018)
The problem of the appearance of the sliding effect in the wheel-road contact in railway transport is considered. It is known that the sliding effect accompanying the rolling process of the wheel is explained by two fundamentally different processes: sliding caused by the loss of traction of the wheel to the road surface and, so-called, deformation sliding. The phenomenon of deformation sliding is not related to loss of adhesion and can occur even when the wheel is fully engaged with the road surface. In fact, the deformation sliding is due to the non-trivial deformation dynamics of the rim of the wheel and the rail which results in an actual reduction or increase in the speed of the translational motion of the wheel while maintaining its angular frequency of rotation. Due to the fact that the phenomenon of loss of adhesion, as well as the accompanying sliding, has been studied in some detail, in this paper attention is focused specifically on the deformation component of the sliding process.